2021
DOI: 10.3390/nu13113672
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Cognitive Dysfunction: New Molecular Concepts and Discrepancies between Animal and Human Findings

Abstract: Purpose of review: increasing evidence suggests that besides the several metabolic, endocrine, and immune functions of 1alpha,25-dihydroxyvitamin D (1,25(OH)2D), the neuronal effects of 1,25(OH)2D should also be considered an essential contributor to the development of cognition in the early years and its maintenance in aging. The developmental disabilities induced by vitamin D deficiency (VDD) include neurological disorders (e.g., attention deficit hyperactivity disorder, autism spectrum disorder, schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 138 publications
(194 reference statements)
0
42
0
Order By: Relevance
“…The Association of low vitamin D levels with diet and obesity has been seen in a study done by Liel et al 18 . In another study, we have found that a high dietary supplement of vitamin D may improve depressive symptoms 19,20 . In another study Young SN suggests the main dietary source of vitamin D is fish, and while the inverse correlation between fish consumption and depression has usually been interpreted as an association between omega-3 unsaturated fats and depression, the role of vitamin D in such dietary studies requires clarification 21 .…”
Section: Discussionmentioning
confidence: 92%
“…The Association of low vitamin D levels with diet and obesity has been seen in a study done by Liel et al 18 . In another study, we have found that a high dietary supplement of vitamin D may improve depressive symptoms 19,20 . In another study Young SN suggests the main dietary source of vitamin D is fish, and while the inverse correlation between fish consumption and depression has usually been interpreted as an association between omega-3 unsaturated fats and depression, the role of vitamin D in such dietary studies requires clarification 21 .…”
Section: Discussionmentioning
confidence: 92%
“…There is evidence of a protective effect of high levels of vitamin D concentrations on cognitive decline, dementia, and Alzheimer's disease in older adults ( 36 , 41 , 68 , 69 ), which is consistent with our findings. The reason for this may be that vitamin D acts as a cognitive protector by controlling oxidative stress, inflammation, and energy metabolism through its own receptor VDR ( 70 , 71 ), but these findings were conducted in preclinical studies, therefore, the improvement effect of vitamin D supplementation is contradictory at this stage. As only a few randomized controlled trials (RCTs) have explored the effect of vitamin D supplementation on cognitive performance in older people, only two RCTs identified an improvement in cognitive function by vitamin D supplementation, and participants had cognitive impairment ( 69 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have used the PubMed/MEDLINE, EMBASE and Psych INFO databases to identify the most relevant study publications, establishing as search criteria the terms: vitamin D, cholecalciferol, Vitamin D exerts its effect through genomic and non-genomic pathways. Genomics is performed through the VDR receptor which is a member of the nuclear transcription factor family, thus influencing gene transcription and regulating the expression of more than 900 genes [6]. Due to positioning in DNA, it is also involved in the expression of numerous protein complexes throughout the body, including the brain.…”
Section: Methodsmentioning
confidence: 99%